Elementary. The second season [videorecording (DVD)] - Miller, Jonny Lee; Liu, Lucy, 1968-; Quinn, Aidan; Hill, Jon Michael; Doyle, Arthur Conan, 1859-1930
Return to the scene of the crime in "Elementary: The Second Season", with all 24 gripping episodes collected on for the first time on DVD in this 6 disc collection. Jonny Lee Miller returns in this modern-day take on Sherlock Holmes, the dangerously eccentric consulting detective who's addicted to impossible cases. Lucy Liu stars as Dr. Joan Watson, his "sober companion" turned partner in detection. Together, they take on some of the strangest crimes New York has ever seen as they assist the police in uncovering clues that unlock the city's sinister secrets. Only to the very sharpest minds do the incredible solutions seem elementary.